2010
DOI: 10.1161/circulationaha.110.973750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV Protease Inhibitors on Progression of Monocrotaline- and Hypoxia-Induced Pulmonary Hypertension in Rats

Abstract: Background-Pulmonary hypertension (PH) is among the complications of HIV infection. Combination antiretroviraltherapy may influence the progression of HIV-related PH. Because Akt signaling is a potential molecular target of HIV protease inhibitors (HPIs), we hypothesized that these drugs altered monocrotaline-and hypoxia-induced PH in rats by downregulating the Akt pathway, thereby inhibiting pulmonary artery smooth muscle cell proliferation. Methods and Results-Daily treatment with each of 3 first-generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
1
33
1
1
Order By: Relevance
“…Activation of mTOR contributes to proliferative lung diseases such as lung cancer and pulmonary hypertension (28)(29)(30)(31), but its potential involvement in degenerative lung diseases such as COPD has not been specifically investigated. Our evidence of mTOR overactivity and increased cell senescence in COPD, combined with the efficacy of rapamycin in decreasing both mTOR activity and cell senescence, point to mTOR activation as a major driver of cell senescence in lungs from patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of mTOR contributes to proliferative lung diseases such as lung cancer and pulmonary hypertension (28)(29)(30)(31), but its potential involvement in degenerative lung diseases such as COPD has not been specifically investigated. Our evidence of mTOR overactivity and increased cell senescence in COPD, combined with the efficacy of rapamycin in decreasing both mTOR activity and cell senescence, point to mTOR activation as a major driver of cell senescence in lungs from patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, SQV and other first generation HIV-PIs have been shown to reduce immunopathology and tissue damage in several experimental models including sepsis (30), pancreatitis (31) and hypoxia-induced pulmonary arterial hypertension (32). A recent clinical trial showed that a 6-month course of SVQ improves proteinurea in steroid-resistant nephrotic syndrome (33).…”
Section: Discussionmentioning
confidence: 99%
“…11 were associated with cell growth, proliferation, and cell metabolism. Among the new findings was increased expression of chloride intracellular channel 4, a multifunctional protein involved in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%